You are dead - James, Peter (The Roy Grace series., 2015)
The last words Nick Walton hears from his fiancee, Logan Somervile, are in a terrified mobile phone call from her. She has just driven into the underground car park beneath the block of flats where they live in Brighton. Then she screams and the phone goes dead. The police are on the scene within minutes, but Logan has vanished, leaving behind her neatly parked car and telephone. That same afternoon, workmen digging up an old asphalt pat in a park in another part of the city, unearth the remains of a young woman in her early twenties, who has been dead for 30 years. At first, to Roy Grace and his team, these two events seem totally unconnected. But then another young woman in Brighton goes missing and another body from the past surfaces. Meanwhile, an eminent London psychiatrist meets with a man who claims to know a piece of information about Logan. Later Roy Grace makes the chilling realization that this one thing is the key to both the past and the present ...Brighton has its first serial killer in over eighty years.